2019
DOI: 10.1073/pnas.1911880116
|View full text |Cite
|
Sign up to set email alerts
|

Intrinsic elasticity of nucleosomes is encoded by histone variants and calibrated by their binding partners

Abstract: Histone variants fine-tune transcription, replication, DNA damage repair, and faithful chromosome segregation. Whether and how nucleosome variants encode unique mechanical properties to their cognate chromatin structures remains elusive. Here, using in silico and in vitro nanoindentation methods, extending to in vivo dissections, we report that histone variant nucleosomes are intrinsically more elastic than their canonical counterparts. Furthermore, binding proteins, which discriminate between histone variant … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

5
82
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
1

Relationship

3
4

Authors

Journals

citations
Cited by 51 publications
(87 citation statements)
references
References 86 publications
5
82
0
Order By: Relevance
“…One logical prediction of a macromolecule with greater intrinsic internal motions is that they are more elastic (lower Young's modulus) than their canonical counterpart. Indeed, this is what was observed [15]. Interestingly, MCA showed that the heterotypic CENP-A:H3.3 nucleosome, which has been observed in cancer cells [81,82], had a Young's modulus in between CENP-A and H3 nucleosomes [80].…”
Section: Computational Advances In Mechanobiology Of Chromatin and Nusupporting
confidence: 62%
See 1 more Smart Citation
“…One logical prediction of a macromolecule with greater intrinsic internal motions is that they are more elastic (lower Young's modulus) than their canonical counterpart. Indeed, this is what was observed [15]. Interestingly, MCA showed that the heterotypic CENP-A:H3.3 nucleosome, which has been observed in cancer cells [81,82], had a Young's modulus in between CENP-A and H3 nucleosomes [80].…”
Section: Computational Advances In Mechanobiology Of Chromatin and Nusupporting
confidence: 62%
“…Elasticity is formally defined by Hooke's law, which states that the strain in a material is proportional to the applied stress within the elastic limit, which is quantified by Young's modulus. Elastic properties of macromolecules are encoded by their quaternary and higher order structures, as either structurally disordered networks of flexible fibers, or structurally ordered macromolecules [14,15]. Chromatin fibers are in the regime of elastomers found elsewhere in nature, yet little is understood about how equivalent mechanical properties might contribute to its function.…”
mentioning
confidence: 99%
“…Interestingly, MCA showed that the heterotypic CENP-A:H3.3 nucleosome, which has been observed in cancer cells (81,82), had a Young's modulus in between CENP-A and H3 nucleosomes (80). Furthermore, the CENP-A binding protein CENP-C suppressed the internal motions, resulting in a higher Young's modulus (15). In addition to histone variants, the linker histone H1 family (83) impact the chromatin fiber dynamics, most notably by inducing chromatin condensation (84).…”
Section: Computational Advances In Mechanobiology Of Chromatin and Numentioning
confidence: 94%
“…Examples of the extrusion idea, whether by mechanical features, or phase transitions, exist in the literature (15,80,(95)(96)(97). First, a recent cryoEM study of tri-nucleosomes showed that a single CENP-A nucleosome flanked by two H3 nucleosomes created an untwisted structure, demonstrating the power of a single nucleosome to alter the "stitch" of the fiber (95).…”
Section: Experimental Advances In Mechanobiology Of Chromatin and Nucmentioning
confidence: 99%
See 1 more Smart Citation